Fatal haemoperitoneum due to ruptured left hepatic artery aneurysm - Latourrette, Federico; Falconi, Luis (Cirugía del Uruguay, 2020)
left hepatic artery, complicated with serious hemoperitoneum caused by the rupture of the aneurysm. I t could be the second case ever to be reported in which the ethiology was a cystic degeneration of the medial coat in an artery other than the aorta. The first case reported was also of the hepatic artery in a curious coincidence. The hystology of the area tributary to the thrombosed artery is shown, and proved to be normal. The paper is divided into the following chapters: pathology, clinical study, diagnosis, treatment. The conditions under which the hepatic artery may be resected or ligated are established. The frequency and the diagnostic difficulties arising from the intrahepatic location of the aneurysm are studied and also the tactic in front of a hemoperitoneum of non diagnosed cause.